An Investigation of Factors Affecting Customers’ Satisfaction in the Supermarket Sector In Ho Chi Minh City (Hcmc) - Vietnam - Khanh Tuan and Premkumar Rajagopal, Vuong (British Journal of Marketing Studies, 2018)
This empirical study was conducted to find out the relationship among four factors such as brand image, service quality, product quality, and price toward customer’s satisfaction in supermarket in HCMC. The qualitative approach was applied to point out the measurement of the scales of factors and the quantitative approach was to test whether these observed variables contributing to these factors or not. After that, the author conducted a survey to customers who go shopping in Co.op Mart and Vinmart. After checking and selecting the suitable samples, the author collected 221 samples to analyze for this study. There was the test for the reliable theoretical framework that was conducted to test whether the hypothesis was supported or not. As a result, based on multiple regression analysis, the theoretical framework was significant and all the hypotheses were accepted. The factor affecting most to customer’s satisfaction was Price, the second one was Service Quality, the third one was Product Quality, and finally one was Brand Image. In general, this research model was conducted properly and valued to study. Supermarkets in HCMC can apply this empirical study to set up their business strategies and improve their customers’ satisfaction in order to enhance competitive competence as well as attract more new customers in the new era.